The Bulgarian Policy in the Black Sea region from 2007 to 2023 - S. T. Tsvetanova (Проблемы постсоветского пространства)
This article reviews the Black Sea policy vector of Bulgaria after its admission to the European Union. EU enlargement to the East in 2007 changed the views of the Black Sea region as a key strategic point, including the attitude of the Union itself. The accession of Bulgaria and Romania to the EU gave the Black Sea a status of «European sea», making it the eastern border of the Union. This change underlined the importance of the region in the context of European policy and security. The article analyzes the main areas of foreign policy of Bulgaria in Black Sea, including strengthening cross-border cooperation, integration into the Euro-Atlantic structures and ensuring maritime and energy security. The aim of the study is to determine the role and place of Bulgaria in the region. This paper is based on the analysis of official documents and scientific publications. The conclusion reached was that the Black Sea region is of increasing importance for the Republic of Bulgaria due to its obligations to protect the external borders of NATO and the EU, as well as the potential of energy resources extraction on the continental shelf. Officially Sofia considers the Black Sea in the context of European and Euro-Atlantic interest, seeking to deepen the cooperation in the fields of economy, trade and security.